Identifying juvenile and sub-adult movements to inform recovery strategies for a high value fishery—European bass (Dicentrarchus labrax). (16th September 2021) - Stamp, Thomas; Clarke, David; Plenty, Shaun; Robbins, Tim; Stewart, James E; West, Elizabeth; Sheehan, Emma
Abstract: The European bass ( Dicentrarchus labrax ) support high value commercial and recreational fisheries, however the Spawning Stock Biomass (SSB) of the northern Atlantic stock (ICES divisions 4.b–c, 7.a, and 7.d–h) has rapidly declined to an unsustainable level. The decline in SSB has been attributed to high fishing pressure combined with poor recruitment. By tracking juvenile fish their spatial ecology can be identified, and appropriate fisheries management policies designed to boost recruitment can be implemented. Using acoustic telemetry 146 sub-adult European bass (25.2–60 cm fork length) were tracked for up to 370 d across three sites in the southwest of the UK. Tagged fish were detected 2 724 548 times (Range: 166–106 393 detections per fish). Linear modelling estimated tagged fish were resident within 2.4–20.1 km of the site where they were first caught for 42.9–75.5% of the year. Some fish were however resident throughout summer and winter. Individual fish were also tracked moving up to 317 km to other coastal sites, 81% of which returned to their original capture site. Fisheries management should account for the high site fidelity displayed by juveniles and sub-adults of this species and coastal nursery sites should be considered essential habitat.